Parvalbumin interneurons in the hippocampal formation of individuals with Alzheimer’s disease: a neuropathological study of abnormal phosphorylated tau in neurons - Merino-Serrais, Paula; Plaza-Alonso, Sergio; Tapia-Gonzalez, Silvia; León-Espinosa, Gonzalo; DeFelipe, Javier (Frontiers in Neuroanatomy, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder in the elderly. Recent efforts have centered on understanding early events that trigger AD, aiming to facilitate early diagnosis and intervention for improved patient outcomes. The traditional histopathological features observed in AD encompass the extracellular accumulation of amyloid-beta protein and the intracellular abnormal phosphorylation of Tau protein (pTau). However, elucidating how these pathological hallmarks ultimately contribute to cognitive deficits remains a complex challenge. While AD is commonly conceptualized as a disorder characterized by synaptic failure, substantial knowledge gaps persist regarding the mechanisms underlying the onset and progression of the disease, underscoring the need for novel and more effective therapeutic approaches. In this context, the impairment of GABAergic paravalbumin (PV+) neurons has been proposed as a crucial factor contributing to neuronal network dysfunction and cognitive decline in AD. The presence of pTau in pyramidal neurons is directly linked to their impairment in AD; however, the effect of pTau in PV+ neurons remains unclear. In this present study, we analyzed the existence of PV+ neurons containing pTau using immunocytochemistry in the hippocampal formation and entorhinal cortex of human samples from diagnosed AD cases and individuals without neurological or psychiatric disorders. Two pTau isoforms, pTauAT8 and pTaupS396, corresponding to early and late stages of AD respectively, were examined. Our findings indicate that most PV+ neurons across the hippocampal formation and entorhinal cortex did not contain pTau in either group cases. Interestingly, while AD cases diagnosed with dementia exhibited a higher number of pTau+ neurons, the majority of PV+/pTau+ neurons were found in individuals with no neurological alterations. This suggests that the presence of pTau in PV+ neurons does not directly correlate with the overall abundance of pTau+ neurons. Given that PV+ neuron impairment is a key pathogenic mechanism in AD and is associated with cognitive decline, understanding the changes in PV+ neurons during AD progression could provide critical insights into the alterations of neuronal circuits underlying the disease.